Challenging the use of adult neuropsychological models for explaining neurodevelopmental disorders: Developed versus developing brains: The 40th Sir Frederick Bartlett Lecture. Issue 1 (January 2013) - Karmiloff-Smith, Annette
In this paper, I contrast approaches from adult neuropsychology that seek selective, domain-specific deficits with approaches aimed at understanding the dynamics of developmental trajectories in children with genetic disorders. I stress the crucial difference between develop ed brains damaged in their mature state, and atypically develop ing brains. I also challenge the search for single genes to explain selective cognitive-level outcomes. Throughout, the paper argues that it is critical to trace cognitive-level deficits back to their basic-level processes in infancy, where genes are likely to exert their early influences, if we are to understand both the impairments and proficiencies displayed in children with neurodevelopmental disorders.